2010
DOI: 10.1159/000321830
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prophylaxis of Hereditary Angioedema with a Pasteurized C1 Inhibitor Concentrate

Abstract: Hereditary angioedema (HAE) is a relatively rare genetic disorder caused by a deficiency of C1 esterase inhibitor (C1-INH). Common clinical presentations are abdominal pain and localized edema of the skin, with laryngeal edema being potentially life-threatening. Replacement therapy with C1-INH concentrate is recommended for treatment of acute HAE attacks and results in rapid resolution of symptoms. C1-INH concentrate can also be used for prophylaxis of HAE and is recommended in cases where standard prophylacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…To focus more clearly on the effect of TA on AE attacks, patients who also took another maintenance treatment (androgen derivatives or C1‐inhibitor concentrate ) and patients treated with progestins were excluded. This last was necessary, as a recent study showed that these could be used effectively as a maintenance treatment, reducing the frequency of attacks.…”
Section: Discussionmentioning
confidence: 99%
“…To focus more clearly on the effect of TA on AE attacks, patients who also took another maintenance treatment (androgen derivatives or C1‐inhibitor concentrate ) and patients treated with progestins were excluded. This last was necessary, as a recent study showed that these could be used effectively as a maintenance treatment, reducing the frequency of attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Dose and/or frequency may need adjustment for optimum control. On-demand therapy (C1-INH concentrate, ecallantide, or icatibant) should be available for all patients on prophylaxis because breakthrough attacks occur in most patients on long-term prophylaxis [35,99-101]. …”
Section: Therapy Of Hae-1/2mentioning
confidence: 99%
“…Se esses medicamentos não forem disponíveis, deverá ser feito plasma fresco congelado é de 10 mL/kg, mas o seu uso é ainda controverso. [17][18][19] Medicamentos como C1-INH, progesterona, andrógenos atenuados particularmente o danazol, e os antifibrinolíticos como o ácido tranexâmico e ácido épsilon-aminocapróico têm sido utilizados de forma eficaz na prevenção de crises. [20][21][22][23] Um novo fármaco, um inibidor da calicreína oral (avoralstat), está em estudo para o tratamento profilático do AEH.…”
Section: Discussionunclassified